Monitoring longitudinal immunological responses to bluetongue virus 17 in experimentally infected sheep - Joseph A Westrich; Erin E McNulty; Molly Carpenter; Mollie Burton; Kirsten Reed; Amy Nalls; Audrey Sandoval; Christie Mayo; Candace K Mathiason (Virus Research, 2023)
Bluetongue virus (BTV) is an economically important pathogen of ruminant species with worldwide prevalence. While many BTV infections are asymptomatic, animals with symptomatic presentation deteriorate quickly with the sickest succumbing to disease within one week. Animals that survive the infection often require months to recover. The immune response to BTV infection is thought to play a central role in controlling the disease. Key to understanding BTV disease is profiling vertebrate host immunological cellular and cytokine responses. Studies to characterize immune responses in ruminants have been limited by a lack of species-specific reagents and assay technology. Here we assess the longitudinal immunological response to experimental BTV-17-California (CA) infection in sheep using the most up to date assays. We infected a cohort of sheep with BTV-17-CA and longitudinally monitored each animal for clinical disease, viremia and specific immunological parameters (B cells, T cells, monocytes) by RT-qPCR, traditional flow cytometry and/or fluorescent based antibody arrays. BTV-inoculated sheep exhibited clinical signs characteristic of bluetongue virus disease. Circulating virus was demonstrated after 8 days post inoculation (DPI) and remained detectable for the remainder of the time course (24 DPI). A distinct lymphopenia was observed between 7 and 14 DPI that rebounded to mock-inoculated control levels at 17 DPI. In addition, we observed increased expression of pro-inflammatory cytokines after 8 DPI. Taken together, we have established a model of BTV infection in sheep and have successfully monitored the longitudinal vertebrate host immunological response and viral infection progression using a combination of traditional methods and cutting-edge technology.